High Performance Liquid Chromatography (HPLC) Method for the Determination of Thiourea in Wheat Flour and Its Products - WANG Qiu; HE Hai-tong; LI Jin-qing; ZHOU Ming-lin; LIU De-qun (Liang you shipin ke-ji, 2022)
This research aimed to establish a determination of thiourea in wheat flour and its products of high performance liquid chromatography (HPLC) method. Thioureas in wheat flour and noodle samples were extracted with pure water under ultrasonic conditions at 25 ℃ for 15 min. After centrifugation and filtration, they were separated by Agilent ZORBAX SB-C18 column with mobile phase of 0.02 mol/L phosphoric acid-disodium hydrogen phosphate buffer solution (pH=3) + methanol =98+2. The detection wavelength was 236 nm, and the quantitative method was external standard. The range of thiourea was 0~20.0 μg/mL and the linear relationship was good (correlation coefficient r=0.999 99). The limit of detection (S/N=3) was 0.5 mg/kg and the limit of quantification (S/N=10) was 1.5 mg/kg. The spiked recovery test and precision test were carried out on wheat flour and surface samples at three levels of method detection limit, 2 times method detection limit and 10 times method detection limit. All the test results met the requirements of spiked recovery and precision in Appendix F of GB/T 27404—2008 <Criterion on Quality Control of Laboratories—— Chemical Testing of Food>. The method was accurate, stable and reliable for the determination of thiourea in wheat flour and its products.